2010
DOI: 10.1016/j.fertnstert.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery improves after weight loss in overweight and obese women with polycystic ovary syndrome

Abstract: Weight loss in overweight and obese women with PCOS is associated with improvements in HRR, which suggests improved autonomic function. This highlights the importance of weight loss to reduce the cardiovascular disease risk in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…In support of our findings, women with PCOS have greater density of ovarian cathecholaminergic nerve fibers (27,53), altered catecholamine metabolism (18), and disturbed HRV (81) and abnormal heart rate recovery (HRR) after exercise test, two indirect markers of autonomic function (20,67,71). Furthermore, PCOS is associated with risk factors thought to be related to altered activity of the sympathetic nervous system, such as hyperinsulinemia, insulin resistance, obesity, and cardiovascular disease (20,31,67,72).…”
Section: Pcos Is Associated With High Sympathetic Nerve Activitysupporting
confidence: 55%
See 1 more Smart Citation
“…In support of our findings, women with PCOS have greater density of ovarian cathecholaminergic nerve fibers (27,53), altered catecholamine metabolism (18), and disturbed HRV (81) and abnormal heart rate recovery (HRR) after exercise test, two indirect markers of autonomic function (20,67,71). Furthermore, PCOS is associated with risk factors thought to be related to altered activity of the sympathetic nervous system, such as hyperinsulinemia, insulin resistance, obesity, and cardiovascular disease (20,31,67,72).…”
Section: Pcos Is Associated With High Sympathetic Nerve Activitysupporting
confidence: 55%
“…However, in a recent study HRR was shown to be improved after body weight loss in women with PCOS (71).…”
Section: Low-frequency Ea and Physical Exercise Decrease Sympathetic mentioning
confidence: 89%
“…Blunted HRR after exercise, a sign of autonomic dysfunction, has been demonstrated to be a strong predictor of all-cause mortality in several studies (Imai et al 1994;Lind and Andren 1999). Moreover, patients with MS and several of its components have been shown to have blunted HRR (Thomson et al 2010). Cardiac autonomic dysfunction and blunted HRR may partly explain increased cardiovascular risk related to the MS.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown improvements for women with PCOS in insulin resistance 19, 20, 36, 37 , serum lipids 36, 38 , and cardiovascular disease risk 19, 20, 36, 39 . Additionally, menstrual cycle improvements have been shown following exercise intervention in women with PCOS 19, 36, 40 .…”
Section: Discussionmentioning
confidence: 99%